Analysis Tolerance of Monosodium Glutamate (MSG) In instant noodles With Uv-Vis Spectrophotometry - Rachma, Firstca Aulia; Saptawati, Tunik (Journal of Science and Technology Research for Pharmacy, 2021)
Background: MSG has become one of the most widely used food flavorings in the world, the FDA (Food and Drug Administration) reported an average per capita intake of MSG in the United States of 550 mg / day in 1973. The use of MSG as a food additive has been regulated by its use. WHO. This rule stipulates that daily consumption of MSG per person should not exceed the safe threshold of 120 mg / kg / day. MSG is proven to be a risk factor for obesity. The increase in body weight in mice occurred after MSG was given as much as 15-30 mg / kg or the equivalent of 1-2 g / person. Based on the description above, it is known that there is a significant influence of MSG in the health sector if consumed in excess. Therefore, researchers are interested in conducting further research related to MSG levels in instant noodle samples in the Semarang city area. Aim: The purpose of this study was to test the MSG levels in instant noodles with a spectrophotometer. Method: The tools used are a UV-Vis spectrophotometer (Shimadzu), NaCl and MSG salts. MSG used in instant noodles, 0.5% Ninhydrin Reagent. Result: MSG levels from each of the 10 samples of instant noodles that are traded in Semarang City, the highest levels are found in sample J of 4.70% and the lowest MSG levels are in sample G of 2.90%. Conclusion: Instant noodles sold in the city of Semarang are positive for Monosodium glutamate (MSG) and The results of quantitative analysis, where the MSG levels contained in each sample of instant noodles in Semarang City show that it is still below the standard for adults.